TEKNIK PENULISAN NASKAH DENGAN MENGOPTIMALKAN UNSUR DRAMATIK DALAM PRODUKSI PROGRAM DOKUMENTER OBSERVASIONAL “URUP” - Regita Wisnu Amelinda; Halimatus Sa’diyah; Sazkia Noor Anggraini (Jurnal Ilmu Komunikasi AKRAB, 2019)
This documentary about the life of Ketoprak Tobong Kelana Bhakti Budaya inYogyakarta. This group is in a critical condition like has minimize income from spectatorsand the actors receive low wages. The main message in this documentary is thededication and love of actors and spectators in an effort to preserve Tobong KelanaBhakti Budaya Ketoprak. Observational style was chosen as the style of deliveringmessages by showing the daily life of Ketoprak Tobong Kelana Bhakti Budaya and theirinteractions with the audience. The script writer strengthens the dramatic element byusing the Dramatik Tension Brand Mathews structure that explains the journey of theKetoprak Tobong Kelana Bhakti Budaya story by having its own emphasis or tension(tension) in each part of the story. This conflict refers to the problem being discussed orfaced. A good arrangement of dramatic tension will prevent it from a monotonous andtedious situation. Script writer use special-general structures using thematic grooves.Futhermore, the visual is sodramatic so that the audience feels curious and reluctantuntil the end of this documentary.